Effect of 180 Days of Water Storage on the Transverse Strength of Acetal Resin Denture Base Material - (:unkn) unknown (WILEY, 2010)
Purpose: Acetal resin has been used as an alternative denture base and clasp material since 1986. The manufacturers claim that acetal resin has superior physical properties when compared to conventional denture base acrylic resins. Limited information is available about transverse strengths of acetal resin. The purpose of this investigation was to compare transverse strengths of pink and white acetal resins to transverse strengths of conventional heat-polymerized polymethylmethacrylate (PMMA) resin in increasing durations of water storage. Materials and Methods: A transverse strength test was performed in accordance with International Standards Organization (ISO) specification No 1567. Twenty 65 x 10 x 2.5 mm(3) specimens of each resin were prepared; five specimens of each resin group were subjected to three-point bending test after 50 hours, 30 days, 60 days, and 180 days of water storage in distilled water at 37 degrees C. Experimental groups' transverse strengths were compared by three-way ANOVA and Duncan's multiple range tests. Results: Transverse strength of PMMA denture base material was found to be in accordance with the requirements of ISO specification No 1567. Transverse strengths of white and pink acetal resin could not be calculated in this study, as white and pink acetal resin specimens did not break at the maximum applied force in the three-point bending test. Flexural strength of acetal resin was found to be within the ISO specification limits. As the water storage time increased, the deflection values of PMMA showed no significant difference (p > 0.05). Both the white and pink acetal resin showed significant increase in deflection as the water storage time was increased from 50 hours to 180 days (p < 0.05). Conclusion: The results of this study indicated that transverse strength values of PMMA were within the ISO specification limit. Water storage time (50 hours, 30, 60, and 180 days) had no statistically significant effect on the transverse strength and deflection of PMMA. Acetal resin suffered from permanent deformation, but did not break in the three-point bending test. Acetal resin showed significant increase in deflection as the water storage time was increased from 50 hours to 180 days. All materials tested demonstrated deflection values in compliance with ISO specification No 1567.
Keywords: Acetal resin; transverse strength; denture base materials; FIBER; FRACTURE; IMPACT; GLASS